The Impact of Beauty Influencers on Local Brand Image - Sudradjat, Ratih Hasanah; Ramadhani, Rhania Shafa (Borong Newinera Publisher, 2025)
This study aims to understand and analyze the influence of Beauty Influencers on the brand image of local products in the digital era. The research employs a quantitative approach using causality and survey methods, involving 100 respondents who are female consumers of the local brand Somethinc in Bandung City. The data was collected as primary data. Data analysis was conducted using simple linear regression, correlation coefficient, and determination coefficient methods, utilizing SPSS software. The results of the study indicate that Beauty Influencers have a significant impact on brand image. These findings emphasize that Beauty Influencers can have a positive impact on the brand image of the local brand Somethinc. This means that as the role of Beauty Influencers increases, the brand image will also improve. Conversely, if the influence of Beauty Influencers decreases, the brand image will also decline. The contribution of Beauty Influencers to the brand image is recorded at 60.1%.